2018
DOI: 10.1136/heartjnl-2017-312559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of general anaesthesia and non-general anaesthesia approach in transfemoral transcatheter aortic valve implantation

Abstract: Procedure outcome, and 30-day and 1-year mortality are not influenced by mode of anaesthesia. However, GA is associated with longer procedure duration and greater length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
20
0
6
Order By: Relevance
“…Although not the primary aim of our investigation, reduced time courses have been shown to effectively reduce costs . Although there might be some high level contemporary departments where the LOS in hospital for patients after TF‐TAVI is somewhere between 1 and 3 days, most of the available literature reports LOS in hospital between 7 and 13 days, which is in agreement with our data …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although not the primary aim of our investigation, reduced time courses have been shown to effectively reduce costs . Although there might be some high level contemporary departments where the LOS in hospital for patients after TF‐TAVI is somewhere between 1 and 3 days, most of the available literature reports LOS in hospital between 7 and 13 days, which is in agreement with our data …”
Section: Discussionsupporting
confidence: 89%
“…34 Although there might be some high level contemporary departments where the LOS in hospital for patients after TF-TAVI is somewhere between 1 and 3 days 35 , most of the available literature reports LOS in hospital between 7 and 13 days, which is in agreement with our data. [36][37][38] The present study has several limitations. This is a single-center observation in a before-after-design with a limited number of patients.…”
Section: Discussionmentioning
confidence: 86%
“…Transkateter aort kapak implantasyonu işlemlerinde anestezik yaklaşımlar, ekibin deneyimine, hastanın sistemik komorbiditelerine ve kapak implantasyonu için seçilmiş yaklaşım tekniklerine bağlı olarak değişmektedir [7,8] . Transkateter aort kapak implantasyonu uygulamaları için GA, loko-rejyonel anestezi, sedasyon ve monitörize anestezi bakımı gibi anestezi yöntemleri tanımlanmıştır [8,9] Bizim çalışmamızda da TAVİ işlemleri için GA, LS ve LM teknikleri kullanılmış olup, her 3 tekniğin de TAVİ işlemi için uygulanabilir olduğu gösterilmiştir.…”
Section: Discussionunclassified
“…Eskandari et al reported that neither the outcome of the procedure nor the 30-day and 1-year mortality rates are affected by the mode of anesthesia. 12 However, in a study that used data from the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry, patients who underwent TAVI with moderate sedation had a significantly lower risk of mortality or stroke at 30 days than those in whom TAVI was performed with the patient under general anesthesia despite of an equivalent procedure success rate. 13 No randomized clinical trial has been conducted to determine the most appropriate type of anesthesia for TAVI, and decisions regarding anesthesia are left to institutional heart teams.…”
Section: Iatrogenic Gastric Tear Caused By Transesophageal Echocardiomentioning
confidence: 99%